Allele Frequencies of STR CODIS 13 of Madura Ethnic from Bangkalan and Probolinggo - Wening Prastowo; Diana Lyrawati; Sri Andarini; Karyono Mintaroem (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2018)
One of forensic identification that can be done is through DNA testing. FBI recommends to use 13 short tandem repeat loci known as CODIS 13 for forensic DNA testing. We tested such system to characterize and determine whether individuals with Madura ethnic background (Madurese) resides in different region differ in CODIS 13 pattern. Employing standard PCR-RFLP for STR CODIS 13 our results showed that indeed the CODIS 13 pattern between the two regions were distinct. Most frequent alleles appeared in Madura ethnic from Bangkalan were at locus D3S1358: allele 16; VWA: 16; FGA: 24 and 26; TH01: 8; TPOX: 9; CSF1PO: 10; D5S818: 11 and 13; D13S317: 14; D7S820: 9; D8S1179: 15; D21S11: 27, 28 and 30; D18S51: 16; and D16S539: 15. Most frequent alleles appeared in each locus of Madura ethnic from Probolinggo were locus D3S1358: allele 17; VWA: 17; FGA: 23 and 26; TH01: 7; TPOX: 10; CSF1PO: 10, 11 and 13; D5S818: 11 and 12; D13S317: 11; D7S820: 11; D8S1179: 11 and 12; D21S11: 30; D18S51: 14; and D16S539: 8. The heterozygosity levels of Madura ethnic from Bangkalan’s CODIS 13 varied from 0.4180 (D5S818) to 0.9102 (FGA). The power of exclusion was between 0.1569 (D5S818) to 0.7667 (FGA). The power of discrimination was between 0.2816 (D5S818) to 0.9811 (FGA). The paternity index was between 0.8591 (D5S818) to 5.5653 (FGA). The heterozygosity index of Madura ethnic from Probolinggo varied between 0.63021 (VWA) to 0.94445 (FGA), power of exclusion was between 0.33418 (VWA) to 0.84779 (FGA), and power of discrimination ranged from 0.60501 (TPOX) to 0.99305 (FGA).